Tata Kelola Kowisata Berbasis Ergonomi dan Kearifan Lokal di Wisata Pulau Oksigen Gili Iyang - Izzuddin, Muchammad Ghozi; Ilahiyah, Inayah (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2022)
This study aims to determine the stages of exploration by stakeholders and local communities regarding the importance of ergonomic ecotourism management through preserving the environment based on local wisdom on Gili Iyang Oxygen Island. Through data collection methods used by interviews, observations, and Focused Group Discussions (FGD), the next stage of the research methodology is action research given to stakeholders, namely members of the Tourism Awareness Group, members of the Prosperous Youth Movement, and local communities. The results of the study indicate that there are potential natural tourism destinations and local wisdom on Oxygen Island Gili I which is very potential to be developed, so it is necessary to pay attention to ergonomics-based ecotourism governance and local wisdom as a form of prevention against environmental risks and safety and tourists, through reflection provided by researchers. Indicated several efforts as an ecotourism management plan entitled ergonomics and local wisdom on Oxygen Island Gili Iyang, Madura. Gili Iyang Oxygen Island manager needs to improve branding as ecotourism based on local wisdom so that ergonomics-based ecotourism and local wisdom on Gill Island are increasingly known and visited. Keywords: Price, Food Quality, Buying Interest